2023
DOI: 10.1063/5.0136290
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the mechanisms of the longitudinal pulsed detonation in two-dimensional rotating detonation combustors

Abstract: A numerical study of the longitudinal pulsed detonation (LPD) is conducted in the present paper. The occurrence mechanism of the LPD, called shock wave amplification by coherent energy release (SWACER) is verified preliminarily in this study. To be specific, upstream propagating shock waves, which originate from the outlet, induce a specific gradient of reactant distribution and then detonation waves are ignited and evolve along the gradient in close succession. It is worth noting that the occurrence of LPD do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Therefore, in this study, NaScH 3 is found to be the best material for hydrogen storage among NaM T H 3 (M T =Sc, Ti, V) hydrides, due to its favorable properties. The population analysis and electron density difference, along with charge density distribution, are vital in exploring the hydrogen storage capacities of lead-free perovskite NaM T H 3 as an efficient solid-state hydrogen storage material [38,39].…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Therefore, in this study, NaScH 3 is found to be the best material for hydrogen storage among NaM T H 3 (M T =Sc, Ti, V) hydrides, due to its favorable properties. The population analysis and electron density difference, along with charge density distribution, are vital in exploring the hydrogen storage capacities of lead-free perovskite NaM T H 3 as an efficient solid-state hydrogen storage material [38,39].…”
Section: Electronic Propertiesmentioning
confidence: 99%